2017
DOI: 10.1093/chromsci/bmx040
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and Validated HPLC Analysis of St. John's Wort Extract and Final Products by Simultaneous Determination of Major Ingredients

Abstract: Aim of this work was to develop a validated high performance liquid chromatography method for the analysis of extracts and final products of St. John's wort, according to international guidelines for bioanalytical method validation. Chromatographic separation was performed on a C18 column with a combination of gradient and isocratic steps; the mobile phase composed of ammonium acetate solution (pH 4.5; 10 mM), acetonitrile and methanol. Quantification and method validation was performed using extract spiked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…An examination of the organometallic structure, crystallite parameters and phase purity of the prepared OM-Ag-NS was performed using an X-ray diffraction (XRD) instrument (X'Pert 3 Powder, PANalytical™). The angle of diffraction (2q) was adjusted between 20 and 80 .…”
Section: Structural and Morphological Examination Of Om-ag-ns Producementioning
confidence: 99%
See 1 more Smart Citation
“…An examination of the organometallic structure, crystallite parameters and phase purity of the prepared OM-Ag-NS was performed using an X-ray diffraction (XRD) instrument (X'Pert 3 Powder, PANalytical™). The angle of diffraction (2q) was adjusted between 20 and 80 .…”
Section: Structural and Morphological Examination Of Om-ag-ns Producementioning
confidence: 99%
“…1,2 Phytochemical analysis of H. perforatum extracts has revealed that they contain a variety of antioxidants with bioactive functional groups. 3 Recent investigations also reported that hyperforin and hypericin obtained from H. perforatum are very effective in photoinduced catalysis, with remarkable activation at room temperature. 4,5 Moreover, the high concentration of avonoids (mainly quercetin and its derivatives) in H. perforatum extracts also endows them with greater antioxidant properties.…”
Section: Introductionmentioning
confidence: 98%
“…The identification of the rest of the compounds (Table 1) was performed by comparison of their mass and UV-vis spectra to those in the literature (peaks 6, 7, 9, 13, 16, 19, 20, 21) (Brolis et al 1998;Tatsis et al 2007;Porzel et al 2014;Zdunic et al 2017;Sarrou et al 2018;Napoli et al 2018); peaks 2-5, 18, and 23-26 were identified at the compound class level and their presence in other Hypericum taxa has been reported earlier (Tanaka et al 2009;Mamemura et al 2011;Porzel et al 2014;Sarrou et al 2018). The spectra of peaks 15 and 17 were the same; HPLC analysis showed that peak 15 had the same elution time with I3,II8-biapigenin (7) in H. perforatum extract (Zeliou et al 2017). This identification was in accordance with Brolis et al (1998), whereas the elution order of I3,II8-biapigenin (7) and amentoflavone reported by Napoli et al (2018) helped us to identify peak 17 as amentoflavone.…”
Section: Resultsmentioning
confidence: 64%
“…Separation was performed on a C18 column (Luna C18: 4.6 mm × 250 mm, 5 μm, Phenomenex, USA) with a coupled guard column cartridge C18 (3 mm × 4 mm, 5 μm, Phenomenex, USA), as earlier described (Zeliou et al 2017). Briefly, quantification of phloroglucinols and flavanols was performed at 270 nm based on the rutin standard curve (2.0-200.0 μg/ml, y = 0.41x + 0.15, R 2 = 0.9977); of caffeoylquinic acid at 300 nm based on chlorogenic acid standard curve (3.0-75.0 μg/ml, y = 0.73x − 1.00, R 2 = 0.9969); of hyperoside (3.0-200.0 μg/ml, y = 0.77x − 0.19, R 2 = 0.9985) and isoquercitrin (2.0-200.0 μg/ml, y = 0.73x -0.37, R 2 = 0.9994) and quercetin (7.2-200 μg/ml, y = 0.85x -3.63, R 2 = 0.9985) at 350 nm based on their standard curves; the quantification analysis of other flavonoids also at 350 nm based on rutin standard curve; and for naphthodianthrones a wavelength at 590 nm, based on hypericin (3.5-80.0 μg/ml, y = 1.63x − 2.38, R 2 = 0.9949) standard curve (Zeliou et al 2017). Reference HPLC standards of chlorogenic acid [3-O-caffeoylquinic acid according to the manufacturer but 5-O-caffeoylquinic acid according to IUPAC numbering (Clifford et al 2017…”
Section: Methodsmentioning
confidence: 99%
“…Hypericum perforatum is an important medicinal plant that belongs to Hypericaceae family and is cultivated worldwide for the extensive use as a therapeutic agent. H. perforatum owns variety of valuable compounds, which have the tremendous antioxidant potential as shown in figure 1 [24,25].…”
Section: Introductionmentioning
confidence: 99%